Building a conservative welfare state in Botswana - Jeremy Seekings (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Botswana's welfare state is both a parsimonious laggard in comparison with some other middle-income countries in Africa (such as Mauritius and South Africa) and extensive (in comparison with its low-income neighbours to the north and east). Coverage is broad but cash transfers are modest. This reflects distinctively conservative features - including, especially, preferences for workfare and for minimal benefits paid in kind (food) rather than cash - combined with parsimonious cash transfers for select categories of deserving poor (the elderly and orphans), administered through the Department of Local Government, not a dedicated welfare department. This is a very different model of welfare state-building - and, more generally, social contract - to those of its neighbours in Southern Africa. It is the result of the specific character of poverty in Botswana and the enduring, but not unchallenged, political dominance of the conservatively paternalist Botswana Democratic Party.
Keywords: P16; I38; O55; H53; J14; Q25; 330; social protection; drought relief; Botswana; conservatism; dependency; welfare state; poverty reduction